The Cox’s Bazar Of Bangladesh - a rising tourist spot in the World: its economic prospects and constraints - Parveen, Jannat Ara; Rajon, Mohammed Shahed (2008)
Currently Cox’s Bazar of Bangladesh has been recognized as a rising tourists’ spot among the fastest growing destinations in the world. Presently it also holds first position in the competition of world’s new seven wonders. In this context, the main initiative of the present study is to focus on the performance of Bangladesh of tourism in general and in Cox’s Bazar as a major tourist spot of the country in particular. The study mainly examines potential tourism products of Cox’s Bazar and its nearer areas, performance of Bangladesh tourism and prevailing constraints and challenges of the same. The study results reveal that Bangladesh has huge prospects to flourish its economy through tourism and world recognized heritage ‘Cox’s Bazar’ has many tourism products to attract world-wide tourists’. But due to lack of resource constraints and other reasons government initiatives are not adequate to develop (specially infrastructure) tourism in the country and so, this industry still unexplored to most potential tourists’ of the world. The study concludes that both government and private interventions are vital one to develop and modernize the Cox’s Bazaar (tourist capital of the country) including other potential spots of Bangladesh.